2009
DOI: 10.2337/db08-1611
|View full text |Cite
|
Sign up to set email alerts
|

Functional Assessment of Pancreatic β-Cell Area in Humans

Abstract: OBJECTIVEβ-Cell mass declines progressively during the course of diabetes, and various antidiabetic treatment regimens have been suggested to modulate β-cell mass. However, imaging methods allowing the monitoring of changes in β-cell mass in vivo have not yet become available. We address whether pancreatic β-cell area can be assessed by functional test of insulin secretion in humans.RESEARCH DESIGN AND METHODSA total of 33 patients with chronic pancreatitis (n = 17), benign pancreatic adenomas (n = 13), and tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
123
2
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(152 citation statements)
references
References 39 publications
17
123
2
10
Order By: Relevance
“…Because of the frequent use of glucose-lowering medication in the patients with diabetes studied herein, it is likely that glucose concentrations of these patients would have been even higher after a drug-washout period. This might explain why the associations between beta cell area and glycaemic control found in this study were weaker than those described in the previous study [34].…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Because of the frequent use of glucose-lowering medication in the patients with diabetes studied herein, it is likely that glucose concentrations of these patients would have been even higher after a drug-washout period. This might explain why the associations between beta cell area and glycaemic control found in this study were weaker than those described in the previous study [34].…”
Section: Discussioncontrasting
confidence: 95%
“…Consistent with such reasoning, the inverse relationship between beta cell area and glycaemic control was no longer detectable when the groups of patients with and without diabetes were studied separately. The present results are in support of our previous study about functional predictors of beta cell area in humans [34]. In that study, an even closer association between glycaemia and beta cell area has been found.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The duration of diabetes at baseline was significantly longer in the insulin-treated group than in the non-insulin-treated group. There was no significant dif- betes [3], and various antidiabetic treatment regimens have been postulated to modulate β-cell mass. To the best of our knowledge, no earlier studies have comprehensively examined the influence of clinical characteristics on the annual decline of β-cell function.…”
Section: Comparison Of Annual Changes Of Fcpr and δCpr (Fig 2)mentioning
confidence: 93%
“…These are based on correlations between functional insulin secretion measurements and beta cell mass [4]. Furthermore, establishment of the beta cell mass by morphometry on biopsies may be grossly misleading owing to the heterogeneity of islet distribution in the organ.…”
mentioning
confidence: 99%